1996
DOI: 10.1037/0022-006x.64.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Depression and smoking cessation: Characteristics of depressed smokers and effects of nicotine replacement.

Abstract: Previous research has linked depression to difficulties in smoking cessation. The authors followed 269 smokers who attempted to quit smoking for 3 months. Participants were given nicotine gum (2 or 4 mg) or placebo gum and brief counseling. The study found that 34% of the smokers met the criterion for current depression using the Center for Epidemiological Studies Depression Scale. Depressed smokers relapsed significantly earlier than the nondepressed. Nicotine gum was significantly more effective than placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
155
2
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(171 citation statements)
references
References 19 publications
8
155
2
6
Order By: Relevance
“…Tal como já foi referido, no nosso estudo, a avaliação passiva, revelou-se como preditora da qualidade de vida mental dos fumadores, corroborando assim, o que é mencionado na literatura. Os fumadores com humor deprimido são menos ativos na utilização de estratégias de coping (Kinnunen, Doherty, Militello & Garvey, 1996) e quando o fazem, tendem a adotar estratégias de evitamento, negação (avaliação passiva) e centradas na emoção, que, segundo Larsen (2000), são ineficazes para a regulação a longo prazo do humor. Relativamente aos abstinentes, concluímos que ter doença respiratória crónica, elevada morbilidade psicológica, bem como maior procura de apoio espiritual predizem pior qualidade de vida física.…”
Section: Discussionunclassified
“…Tal como já foi referido, no nosso estudo, a avaliação passiva, revelou-se como preditora da qualidade de vida mental dos fumadores, corroborando assim, o que é mencionado na literatura. Os fumadores com humor deprimido são menos ativos na utilização de estratégias de coping (Kinnunen, Doherty, Militello & Garvey, 1996) e quando o fazem, tendem a adotar estratégias de evitamento, negação (avaliação passiva) e centradas na emoção, que, segundo Larsen (2000), são ineficazes para a regulação a longo prazo do humor. Relativamente aos abstinentes, concluímos que ter doença respiratória crónica, elevada morbilidade psicológica, bem como maior procura de apoio espiritual predizem pior qualidade de vida física.…”
Section: Discussionunclassified
“…12,46 Empiric evidence suggests that the heightened sensitivity of some depressed individuals to nicotine's positive mood-altering effects may lead to selfmedication, which reinforces regular and heavy smoking. [57][58][59][60][61][62][63] Both survey and experimental studies report that nicotine reduces negative mood in smokers, that negative mood within 3 days of attempting to quit is one of the strongest predictors of relapse, that the benefits of nicotine gum are more apparent in depressed smokers, 9,46,64 and that persistent withdrawal symptoms predict major depression following smoking cessation. 65 Even though all retrospective studies indicate that negative mood is a precipitant of relapse, 12 and thereby might maintain an active smoking habit, recall bias may play an important role in the association.…”
mentioning
confidence: 99%
“…1 Although the nature of the relation between cigarette smoking and disease has been most convincingly demonstrated for physical illness, several researchers have linked smoking to mental illness, especially depression. [2][3][4][5][6][7][8][9][10][11][12][13][14] Almost a dozen studies have shown a significant association between smoking and suicide. However, many of these studies were small and did not control for characteristics common to both smokers and persons who commit suicide.…”
mentioning
confidence: 99%
“…En cuanto al efecto de la sintomatología depresiva al inicio del tratamiento, los resultados coinciden con los hallazgos de otros estudios realizados en contextos no laborales 19 , siendo el efecto independiente de la presencia de historia de TDM contrariamente a lo que algunos estudios habían apuntado 16 . En cuanto al efecto de los antecedentes de TDM, los resultados discrepan de los resultados publicados por algunos estudios previos 8, 9, 10, 11 pero son coherentes con las revisiones más recientes 18 , y una vez más se confirma la coincidencia con resultados de estudios realizados fuera del contexto laboral.…”
Section: Discussionunclassified
“…Por otro lado, la evidencia apunta hacia una relación directa entre sintomatología depresiva al inicio del tratamiento de deshabituación tabáquica con una mayor severidad de dependencia y peores resultados a corto plazo 19 . Otros estudios han concretado que dicha sintomatología predice el fracaso terapéutico solamente en fumadores con antecedentes de TDM, mientras la relación sería inexistente en sujetos sin historia previa 16 .…”
Section: Resumen Abstractunclassified